2013
DOI: 10.1136/bmj.f540
|View full text |Cite
|
Sign up to set email alerts
|

Influence of initial severity of depression on effectiveness of low intensity interventions: meta-analysis of individual patient data

Abstract: Objective To assess how initial severity of depression affects the benefit derived from low intensity interventions for depression.Design Meta-analysis of individual patient data from 16 datasets comparing low intensity interventions with usual care.Setting Primary care and community settings.Participants 2470 patients with depression.Interventions Low intensity interventions for depression (such as guided self help by means of written materials and limited professional support, and internet delivered interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
217
4
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(266 citation statements)
references
References 61 publications
37
217
4
8
Order By: Relevance
“…A recent study found that mild depressive symptoms were associated with lower effect sizes in low-intensity interventions when compared to effects for individuals with at least moderate symptoms (68). Moderator analyses should thus clarify which subgroups of participants benefit the most and the extent to which they benefit from iPST.…”
Section: Study Limitationsmentioning
confidence: 99%
“…A recent study found that mild depressive symptoms were associated with lower effect sizes in low-intensity interventions when compared to effects for individuals with at least moderate symptoms (68). Moderator analyses should thus clarify which subgroups of participants benefit the most and the extent to which they benefit from iPST.…”
Section: Study Limitationsmentioning
confidence: 99%
“…However, in another study baseline severity of depression was not related to the effect of computerized CBT (Proudfoot et al, 2003). A recent meta-analysis of individual patient data assessed the effect of depression severity at baseline for low-intensity interventions such as guided self-help via books and the Internet (Bower et al, 2013). Results showed that patients with more severe depression at baseline demonstrate larger treatment effects than those who are less severely depressed.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that patients with more severe depression at baseline demonstrate larger treatment effects than those who are less severely depressed. However, high initial scores would mean that many patients remain symptomatic after treatment and do not meet criteria for recovery (Bower et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrate comparative effect sizes of improvement in severe depressive symptoms to those experienced in a mild to moderately depressed group, supporting the use of iCBT for severe depression [12,21]. Over half of the participants who provided pre and post treatment data experienced reliable improvement by participating in the intervention (n = 21), supporting the potential for iCBT as an effective measure in this population.…”
Section: Discussionmentioning
confidence: 65%
“…Innovative attempts to overcome these barriers have led to the development of internet-delivered psychological interventions, primarily based on cognitive-behavioural principles (iCBT) for the treatment of depression and other mental health disorders [12]. Internet-delivered interventions overcome some barriers associated with traditional treatment methods [13].…”
Section: Internet-delivered Interventionsmentioning
confidence: 99%